The Role of Bappeda in Regional Development Planning and Policies - Andri Jasman; Yulianto Yulianto; Tina Kartika (Al-Makki Publisher, 2025)
The Regional Development Planning Agency is an institution that assists regional heads in determining regional development policies. The John M. Bryson concept emphasizes a systematic approach to formulating, implementing, and evaluating development policies with formal authority, information centers, and strategic decision-making. This research aims to analyze Bappeda’s role through its formal authority, function as an information center, and strategic decision-making, while identifying supporting and inhibiting factors in the policy formulation process. This study uses a descriptive qualitative research approach, employing data collection techniques through interviews and related documents. The results show that the role of the institution in formulating policies—through formal authority, information centers, and strategic decisions—runs well based on bottom-up principles. The supporting aspects include the commitment of regional leaders and the active involvement of the community, while the inhibiting aspects are the lack of human resources and supporting facilities. The research contributes to the theoretical understanding of regional development planning and offers practical recommendations for local governments to strengthen Bappeda’s role in achieving sustainable development goals.